2021
DOI: 10.1021/acs.inorgchem.0c03740
|View full text |Cite
|
Sign up to set email alerts
|

Frustrated Packing in Simple Structures: Chemical Pressure Hindrance to Isolobal Bonds in the TiAl3 type and ZrAl2.6Sn0.4

Abstract: While simple close-packed arrangements convey a sense of optimization, they can, in fact, host competition between different types of interactions. The TiAl3 structure type, for example, represents one of a series of ordered TE3 variants (T = transition metal, E = main group element) of the face-centered cubic structure, alongside the AuCu3 and ZrAl3 types. These structures differ in their T-T connectivity corresponding to the 18–n rule: electronic pseudogaps occur at electron concentrations of 18–n/T atom, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…For the expanded unit cell, the localized electron count for each site is tuned so that all the atoms experience equal negative atomic CPs, while for the contracted unit cell, these localized counts are adjusted so that all atoms bear the same amount of positive CP. We have found that using an average of the localized electron counts for each atom in the expanded and contracted auxiliary CP calculations leads consistently to physically meaningful CP schemes for the equilibrium structure [25,36].…”
Section: Calibrating the Localized Electron Countmentioning
confidence: 90%
See 1 more Smart Citation
“…For the expanded unit cell, the localized electron count for each site is tuned so that all the atoms experience equal negative atomic CPs, while for the contracted unit cell, these localized counts are adjusted so that all atoms bear the same amount of positive CP. We have found that using an average of the localized electron counts for each atom in the expanded and contracted auxiliary CP calculations leads consistently to physically meaningful CP schemes for the equilibrium structure [25,36].…”
Section: Calibrating the Localized Electron Countmentioning
confidence: 90%
“…This method is based on the recognition that non-optimal interatomic distances are detectable in the local pressures that surround the atoms of a solid-state lattice, as constructed from the output of DFT calculations. In the study of a variety of intermetallic phases, CP analysis has provided explanations for diverse structural phenomena, such as the insertion of interfaces into simple structures [19,20,24,25], the adoption of local icosahedral symmetry in quasicrystal approximants [26][27][28], the emergence in incommensurability [29][30][31][32][33][34], the stabilizing effects of various kinds of single point substitutions [23][24][25]35,36], and the formation of intergrowth structures [27,35,[37][38][39]. The CP maps generated in the process can also be used to analyze the forces involved in chemical bonding and molecular structure [40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of specific site preference [22–27] in the pseudo‐binary/ ternary system motivates us to reinvestigate InPd 3‐x Cu x (x=0–1). In this report, the InPd 3‐x Cu x (x=0–1) were synthesized by conventional high temperature method, and crystal structures were reinvestigated by single crystal and powder X‐ray diffraction and first‐principles electronic structure calculations.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24] Another interesting example of selective substitution was recently reported by Osman and Bobev, where Zn selectively substitutes one of the Li-positions in Li 15 Ge 4 and forms Li 14 ZnGe 4 . [25] The importance of specific site preference [22][23][24][25][26][27] in the pseudo-binary/ ternary system motivates us to reinvestigate InPd 3-x Cu x (x = 0-1). In this report, the InPd 3-x Cu x (x = 0-1) were synthesized by conventional high temperature method, and crystal structures were reinvestigated by single crystal and powder X-ray diffraction and first-principles electronic structure calculations.…”
Section: Introductionmentioning
confidence: 99%
“…In its focus on how interatomic interactions would be influenced by expansion or contraction of a structure, the CP method complements other tools, such as the crystal orbital Hamilton population , or electron localization function/localizability indicator, which offer detailed analyses of the electronic structure for a static geometry. The CP distributions created with this approach can elucidate a variety of phenomena, including the formation of superstructures, , soft phonon modes, incommensurate modulations, ,, substitution patterns, and the forces underlying chemical bonds. In terms of the FK phases, CP analysis has previously accounted for the formation and elemental site preferences of the FK phases μ-Mo 6 Fe 7 and χ-Mo 5 Cr 6 Fe 18 …”
Section: Introductionmentioning
confidence: 99%